Retail Banking Awareness: An Empirical Analysis (with Special Reference to Private Sector Banks) - Bhayani, Sanjay J. (Indian Journal of Marketing, 2005)
Now a day, banking is the most important of the world's economy. The banking functions are the routine functions of one life, which is inevitable, and this one expects to the best, convenient and speedier. The emergence of private sector banks has changed the whole scenario of the banking functions in the recent years. Banks nowadays plans to lay greater stress on consumer banking in the coming years, with a view to achieve higher marker penetration and profitability. Technology has paved the way for expanding the horizon of consumer banking and has smartened up the staid business of banking. In the pre-liberalization days, banking was considered as a chore you would like to finish off as quickly as possible. Today the scenario is totally different. Banks driven by the ever-growing competition have improvised on existing features and created new facilities that are more customers friendly. Growing Indian middle class today has a disposable surplus income and aspires for a better lifestyle. The busy business executive needs cash at any time, at all places and is willing to pay extra for this service. New breed of financial services brand viz. convenience banking, anywhere banking, tele-banking, branchless banking and on-line banking have appeared on the banking landscape. Most of the private and foreign banks have linked up their branches enabling a customer to operate his account from any, even from different cities.